Внутрішньопартійні відносини у процесі посткомуністичних трансформацій - Кройтор, Артем Вікторович; Кройтор, Артем Викторович; Krojtor, А. (My University, 2013)
The article deals with topical issues of political science – the study of the interaction between the party leadership and members of political parties in post-communist transformations. Analyzed the historical origins of internal interaction. Determined that the intra-relationship is an important factor in the democratization of the political system.
Кройтор А. В. Внутрішньопартійні відносини у процесі посткомуністичних трансформацій / А. В. Кройтор // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 301-308.
Keywords: взаємодія між партійним керівництвом та членами політичної партії; посткомуністичні трансформації; історична генеза внутрішньопартійної взаємодії; демократизація політичної системи; взаимодействие между партийным руководством и членами политической партии; посткоммунистические трансформации; исторический генезис внутрипартийного взаимодействия; демократизация политической системы.; the interaction between the party leadership and members of the political party; post-communist transformation; the historical genesis of intra-party cooperation; the democratization of the political system